2019
DOI: 10.1038/s41419-019-1738-3
|View full text |Cite
|
Sign up to set email alerts
|

Long noncoding RNA ANCR inhibits the differentiation of mesenchymal stem cells toward definitive endoderm by facilitating the association of PTBP1 with ID2

Abstract: The generation of definitive endoderm (DE) cells in sufficient numbers is a prerequisite for cell-replacement therapy for liver and pancreatic diseases. Previously, we reported that human adipose-derived mesenchymal stem cells (hAMSCs) can be induced to DE lineages and subsequent functional cells. Clarifying the regulatory mechanisms underlying the fate conversion from hAMSCs to DE is helpful for developing new strategies to improve the differentiation efficiency from hAMSCs to DE organs. Long noncoding RNAs (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
19
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 22 publications
(20 citation statements)
references
References 57 publications
1
19
0
Order By: Relevance
“…As the majority of LYPLAL1-AS1 was present in the cytoplasm (>70%), we speculate that LYPLAL1-AS1 might be a downstream effector of DSP at the post-transcriptional level. Thus, to evaluate the effect of DSP on LYPLAL1-AS1 mRNA stability, hAMSCs transfected with si-NC or si-DSP were treated with actinomycin D (5 μg/ml), which inhibits RNA polymerase and blocks transcription 17 . Knockdown of DSP improved the RNA stability of LYPLAL1-AS1 (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…As the majority of LYPLAL1-AS1 was present in the cytoplasm (>70%), we speculate that LYPLAL1-AS1 might be a downstream effector of DSP at the post-transcriptional level. Thus, to evaluate the effect of DSP on LYPLAL1-AS1 mRNA stability, hAMSCs transfected with si-NC or si-DSP were treated with actinomycin D (5 μg/ml), which inhibits RNA polymerase and blocks transcription 17 . Knockdown of DSP improved the RNA stability of LYPLAL1-AS1 (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…After Pnky and PTBP1 were knocked down respectively, it was found through DEX-Seq 28 sequencing that there were a common part of transcription alterations that affect the differentiation of NSCs and regulate neurogenesis and neuronal development 26 . A new study has shown that PTBP1 can bind and stabilize ID2 mRNA by interacting with lncRNA ANCR, thus inhibiting the differentiation of human adipogenic mesenchymal stem cells (hAMSCs) into defined endoderm cells and reducing the occurrence of liver and pancreatic diseases 29 .…”
Section: Hnrnps Regulate Mrna Stability and Gene Transcription In Stementioning
confidence: 99%
“…Embryonic stem cells differentiate into more specialized cell types to form specific organs by regulating specific gene expression and cell signaling events. Many lncRNAs have been found to regulate signaling molecules in development and differentiation of all the three germ layers to form organs [31]. Those lncRNAs are functionally divergent and perform crucial roles in the generation of cellular diversity and organ complexity during evolution [32].…”
Section: Lncrnas In Developmentmentioning
confidence: 99%